2024
DOI: 10.35848/1347-4065/ad2fe2
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching memory using buckybowl sumanene-inserted bilayer graphene

Eito Ashihara,
Ryoichi Kawai,
Ryousuke Ishikawa
et al.

Abstract: The bowl-shaped molecules of the nanocarbon material, called sumanene, have structural flexibility (bowl inversion). In the case of the sumanene molecule used as an intercalant between graphene layers, it has been predicted that holes and electrons are unevenly distributed according to the bowl inversion. Using the property of sumanene molecules, we expected that resistive switching for the nonvolatile memory applications could be achieved by the sumanene-inserted bilayer graphene. In this study, MIM devices w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…43,44) Following these theoretical predictions, experimental studies have confirmed that sumanene-intercalated bilayer graphene can operate as a resistive switching device through control over the sumanene conformation with a gate electric field. 45,46) Recently, a unique sumanene derivative, monofluorosumanene, has been synthesized by the substitution of one hydrogen atom terminating the benzylic edges of sumanene by an F atom. 47) Thus, monofluorosumanene has structural asymmetry with respect to the fluorination site in the curved C-C network.…”
Section: Introductionmentioning
confidence: 99%
“…43,44) Following these theoretical predictions, experimental studies have confirmed that sumanene-intercalated bilayer graphene can operate as a resistive switching device through control over the sumanene conformation with a gate electric field. 45,46) Recently, a unique sumanene derivative, monofluorosumanene, has been synthesized by the substitution of one hydrogen atom terminating the benzylic edges of sumanene by an F atom. 47) Thus, monofluorosumanene has structural asymmetry with respect to the fluorination site in the curved C-C network.…”
Section: Introductionmentioning
confidence: 99%